2013
DOI: 10.1558/cj.v22i3.399-431
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous CMC and Pragmatic Development

Abstract: This study systematically examines the strength of the connection between synchronous CMC and pragmatic instruction by measuring the effects of three types of synchronous group discussion (written chat [WC], oral chat [OC], and traditional face-to-face [FF] discussion) on the acquisition of the speech act (refusals of an invitation) in the target language. Zhao (2003) notes that CMC research is limited in terms of investigating the effects these types of discussions have on other features of language developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(81 citation statements)
references
References 36 publications
(54 reference statements)
2
75
0
4
Order By: Relevance
“…Reiterating Ngan's (03) reply that she could 'talk' much more in the chat, Yen (03) explained that "… everyone had opportunities to talk; everyone shared equal amount of talk; everyone feels that they must talk". What is more, there were at least three students who claimed their most preferred attribute in the chat was that they could roll back and review what was just discussed, thereby helping increase their monitoring of language usage (Sykes, 2005) and "make language manipulable" (O'Rourke, 2008, p. 232). Other students commented on the feature of place independence of the SCMC (Luppicini, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Reiterating Ngan's (03) reply that she could 'talk' much more in the chat, Yen (03) explained that "… everyone had opportunities to talk; everyone shared equal amount of talk; everyone feels that they must talk". What is more, there were at least three students who claimed their most preferred attribute in the chat was that they could roll back and review what was just discussed, thereby helping increase their monitoring of language usage (Sykes, 2005) and "make language manipulable" (O'Rourke, 2008, p. 232). Other students commented on the feature of place independence of the SCMC (Luppicini, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Simply because Second Life can support voice does not mean that it is always the most appropriate medium for the learning outcomes being targeted. Indeed, the research literature from language education in general and computer-mediated language education in particular reveals that writing not only improves written language skills, but also facilitates orality as well as linguistic and metalinguistic awareness (Beauvois, 1998;Chun & Plass, 2000;O'Rourke, 2005;Schwienhorst, 2002;Sykes, 2005;Thorne, 2008;Wells, 1981). Ma's (1996) research in text-based virtual worlds also revealed a greater level of self-disclosure, egalitarianism and intercultural awareness than found in face to face exchanges between East Asian and North American college students.…”
Section: Affordances Of Virtual Worlds For Language Learningmentioning
confidence: 99%
“…Research has shown that pragmatics is indeed teachable and should be included in L2 language learning (Cohen, 1996;Kasper, 1997;LoCastro, 2003;Rose & Kasper, 2001;Rose, 2005). Furthermore, internet-mediated tools offer immense potential to overcome some of the inherent difficulties in teaching pragmatics (Sykes, 2005). Some of these difficulties include: (a) individual personality differences and sensitivity to certain contextual factors influencing the interaction (Bardovi-Harlig, 2001;Kasper, 1997), (b) assessment and feedback challenges (Cohen, 2004;Roever, 2004;Salaberry & Cohen, 2006), and (c) immense variation (dialect, social, individual) (Márquez-Reiter & Placencia, 2005).…”
Section: Advantagesmentioning
confidence: 99%